2007
DOI: 10.1111/j.1750-2659.2007.00027.x
|View full text |Cite
|
Sign up to set email alerts
|

Chloroquine is effective against influenza A virus in vitro but not in vivo

Abstract: Background  Chloroquine is an inexpensive and widely available 9‐aminoquinolone used in the management of malaria. Recently, in vitro assays suggest that chloroquine may have utility in the treatment of several viral infections including influenza. Objectives  We sought to test whether chloroquine is effective against influenza in vivo in relevant animal models. Methods  The effectiveness of chloroquine at preventing or ameliorating influenza following viral challenge was assessed in established mouse and ferr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 16 publications
3
56
0
2
Order By: Relevance
“…Obviously, there is a difference between the in vivo and the in vitro results achieved with chloroquine treatment of NiV infection, but the reason for the discrepancy is unknown. However, a similar outcome has been reported for influenza treatment with chloroquine (22).…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…Obviously, there is a difference between the in vivo and the in vitro results achieved with chloroquine treatment of NiV infection, but the reason for the discrepancy is unknown. However, a similar outcome has been reported for influenza treatment with chloroquine (22).…”
mentioning
confidence: 62%
“…This dose was chosen based on a previous study of chloroquine treatment in humans suffering from acute malaria (3) and is twice the dose used in a study to determine the effect of chloroquine on influenza infection in ferrets (22). Ferrets 1 to 3 received a loading dose of chloroquine 24 h before viral challenge, and ferrets 4 to 6 received their first dose of chloroquine 10 h after viral challenge.…”
Section: Hendra Virus and Nipah Virus Two Zoonotic Paramyxoviruses Imentioning
confidence: 99%
“…The lead compound RO5464466 and its 2-chloro analogue RO5487624 can effectively prevent the infection of influenza A/Weiss/43 strain (H1N1) with EC50 values of 210 and 86 nM, respectively. In vivo data suggest that RO5487624 has a protective effect on mice that were lethally challenged with influenza H1N1 virus [66]. Mechanism of action studies indicated that these compounds inhibit the virus membrane fusion with host endosome membrane by binding to HA and stabilizing the prefusion HA structure.…”
Section: Antivirals Targeting Ha2mentioning
confidence: 99%
“…Also, the mechanism of action of chloroquine in viral replication is not well known and seems to vary according to the target virus. Discrepancy between in vitro and in vivo efficacy of chloroquine has also been reported for viruses such as influenza [201], severe acute respiratory syndrome (SARS) [202], HIV [203] and Chikungunya [204]. Chloroquine also has immunomodulatory effects (see [199]) that may not favor host’s immunological response against viral infections.…”
Section: Antiviral Strategiesmentioning
confidence: 99%